Thermal and exhumation history of the Eocene Chumstick Basin, Washington State, USA. Issue 5 (13th May 2015) - Enkelmann, Eva; Ehlers, Todd A.; Merli, Gabriel; Methner, Katharina
Abstract This study investigates the Cenozoic evolution of the Cascades Mountains, USA, by means of reconstructing the thermal history of the Chumstick Basin deposits that are located on the eastern flank of the orogen. We present new detrital apatite (U‐Th‐Sm)/He and detrital apatite fission‐track ages from the middle Eocene (~48–37 Ma) Chumstick Formation and modern river detritus. These data are integrated with the published thermochronometric ages of the adjoining Cascade Mountains basement. The new thermochronometer results are combined with existing vitrinite reflectance data for modeling of the basin's thermal history. Results suggest constant temperatures throughout the late Oligocene to early Miocene followed by rapid cooling since 17–10 Ma. Results indicate that the middle to late Miocene uplift of the Cascades resulted in reactivation of the fault zones bounding the Chumstick Basin. The structural reactivation and the weaker lithology of the basin strata in comparison to the harder and more resistant basement rocks of the Cascades resulted in significant basin exhumation. This interpretation is determined from younger apatite (U‐Th‐Sm)/He cooling ages observed in the reset detrital bedrock of the Chumstick Formation than in the adjoining basement rocks. These observations suggest a structural and lithological control on exhumation magnitudes in this region.